Educators’ Adoption of Green Digital Technologies: The Role of Psychological Readiness, Digital Competence, and Institutional Support - Harisa Mardiana (CV. Media Digital Publikasi Indonesia, 2025)
The growing emphasis on sustainability within education requires teachers to integrate environmentally responsible technologies in their teaching practices. This study examines educators’ adoption of green digital technologies by exploring the influence of psychological readiness, digital competence, and institutional support. Grounded in the Technology Acceptance Model (TAM) and the Technological Pedagogical Content Knowledge (TPACK) framework, the research develops a conceptual model that connects individual readiness with professional and institutional enablers. Using a cross-sectional design and data from 200 educators in Indonesia, the findings demonstrate that digital competence and institutional support significantly influence sustainable technology adoption, with psychological readiness acting as a mediator. This study highlights the importance of aligning technological innovation with sustainability goals and provides implications for teacher professional development, institutional policy, and sustainable education strategies.